Effect of postharvest melatonin and salicylic acid applications on quality characteristics and primary and secondary metabolite physiology of tomato fruits - Tansel Kaygısız; Fatih Sen; Muttalip Gundogdu; Shaghef Ejaz; Erdal Aglar (BMC Plant Biology)
Abstract Background This study aims to investigate the effects of postharvest melatonin (ML) and salicylic acid (SA) applications on fruit quality and biochemical properties in tomatoes. The potential synergistic effects were investigated by applying these compounds to the ‘Depar’ tomato variety grown in Bolu in the 2024 production season. The tomato fruit that were mature and free from physical damage were selected and sterilized according to predetermined criteria. Afterwards, ML and SA solutions (1 mM) were sprayed on each fruit and then the fruit were stored at 5 ± 0.5 °C and 90 ± 5% relative humidity. Pomological and biochemical measurements and analyses were carried out on fruit stored for 24 days in three different periods (8th, 16th and 24th days). Results With the extension of storage period, the increase in spoilage and ripening symptoms such as weight loss (8.53%), pH increase (5.01) and soluble solids content (SSC) accumulation (4.95%) was observed in tomatoes. In addition, the significant decreases occurred in malic acid, citric acid, tartaric acid, oxalic acid, vitamin C and phenolic compounds. However, SA and ML applications slowed down these negative changes, with the best results generally obtained in the SA + ML combination. This combination significantly limited the decreases in weight loss and chemical contents, delayed the ripening of tomatoes and maintained their nutritional value. Especially in early and middle storage periods (8th and 16th days of the cold storage), SA + ML applications gave the most effective results. However, some protective effects were reduced by the 24th day the cold storage. Conclusion SA and ML applications are recommended as an effective biopreservation strategy to extend the shelf life of tomatoes, prevent commercial value loss and maintain quality. This study demonstrates the potential of using bioactive compounds to preserve the quality and nutritional values of tomatoes after harvest.